Consenso internacional de opciones terapéuticas en cefalea tensional - Fortes Lopes, Zenaida (Machala : Universidad Técnica de Machala, 2018)
Tension Headache is the most common primary headache that constitutes a public health problem, mainly in primary health care. It presents a high prevalence, a great impact on the quality of life of people and a degree of disability that translates in to socioeconomic cost. It is present in both sexes but it is commonly more frequent in women. It is characterized by bilateral oppressive pain of mild to moderate intensity, has an episodic - chronic character, is not accompanied by nausea, vomiting, photophobia, or buzzing, is not modified by physical activity and is associated with some type of tension mental or muscular Objective: The present work seeks therapeutic options to determine unified information regarding treatment. Materials and methods: A systematic database search was carried out as diagnostic and therapeutic guidelines of the Spanish Society of Neurology, Mexican neuroscience journal, GPC guidelines, ScientDirect, Cochrane, and III Edition of the International Classification of Headache. The criteria of the last 5 years related to tension-type headache have been considered. Conclusions: Within the international consensus of therapeutic options there is a variety of treatments aimed at preventing and treating tension headache.
La Cefalea tensional es la cefalea primaria más habitual que constituye un problema de salud pública, principalmente en la atención primaria de la salud. Presenta una alta prevalencia, una gran repercusión en la calidad de vida de las personas y un grado de discapacidad que se traduce en el costo socioeconómico. Se presenta en ambos sexos pero es comúnmente más frecuente en las mujeres. Esta caracterizado por un dolor opresivo bilateral de leve a moderada intensidad, tiene un carácter episódico - crónico, no se acompaña de nauseas, ni vómito, ni fotofobia, ni zumbido, no se modifica con la actividad física y se asocia con algún tipo de tensión mental o muscular. Objetivo: El Presente trabajo busca las opciones terapéuticas para determinar información unificada respecto al tratamiento. Materiales y métodos: Se realizó una búsqueda sistemática en base de datos como guías diagnósticas y terapéuticas de la Sociedad Española de Neurología, revista mexicana de neurociencia, guías GPC, ScientDirect, Cochrane, y III Edición de la Clasificación Internacional de las Cefaleas. Se han considerado los criterios de los últimos 5 años relacionados con la cefalea tensional. Conclusiones: Dentro del consenso internacional de opciones terapéuticas existe una variedad de tratamientos destinados a prevenir y tratar la cefalea tensional.
Keywords: CEFALEA; SALUD PUBLICA; ATENCION PRIMARIA; CALIDAD DE VIDA